Exceptional selling : - Thull, Jeff (John Wiley, 2006)
This is the first book to apply powerful diagnostic principles directly to sales conversations. It shows you how to create a customer engagement in which the common barriers to success - limited access, ambiguous words, objections, and cutthroat negotiations - melt away